2009
DOI: 10.1111/j.1532-849x.2009.00498.x
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Loads of All‐Ceramic Crowns under Wet and Dry Fatigue Conditions

Abstract: Fracture load of the three ceramic systems was found to be influenced by ceramic composition. Moreover, cement and fatigue condition influenced the fracture loads of the crown specimens evaluated in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 26 publications
6
44
0
1
Order By: Relevance
“…It was reported that adhesive bonding significantly increased fracture strength and improved marginal seal of all-ceramic crowns (Blatz et al 2008;Borges et al 2009;Lu et al 2013;Kern 2015). Furthermore, restorative adhesive complexes should form a ÒmonoblockÓ to ensure long-lasting restorations (Schwartz & Robbins, 2004;Tay & Pashley, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that adhesive bonding significantly increased fracture strength and improved marginal seal of all-ceramic crowns (Blatz et al 2008;Borges et al 2009;Lu et al 2013;Kern 2015). Furthermore, restorative adhesive complexes should form a ÒmonoblockÓ to ensure long-lasting restorations (Schwartz & Robbins, 2004;Tay & Pashley, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In the same study no difference was found in fracture load values between different cementation processes for zirconia 13) . The influence of the cementation mode on lithium disilicate is controversially discussed 12,13) . In the present study an increase in fracture load was found for lithium disilicate, feldspar ceramic and polymer-infiltrated ceramic depending on the compressive strength of the cement.…”
Section: Influence Of the Cement On The Fracture Loadmentioning
confidence: 99%
“…To predict clinical behavior of restorations, fracture load tests on crowns are performed although their significance is controversially discussed [9][10][11][12][13][14][15] . Due to differences in test set up, fracture load of restorative materials can vary significantly [10][11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the restorations for fracture load tests are differently cemented in various studies [1][2][3][4] . Zinc oxide-phosphate, glass ionomer or adhesive cements are used [1][2][3][4][5][6][7][8] . Zirconia shows high values of flexural strength 9) ; lithium disilicate exhibits lower flexural strength than zirconia 10) .…”
Section: Introductionmentioning
confidence: 99%